Peran Supervisor dalam Manajemen Kelas - Endah Tri Wisudaningsih (LP3M Universitas Islam Zainul Hasan Genggong, 2019)
One indicator states that professional teachers / educators have the ability to manage classes, namely providing a conducive atmosphere for effective and efficient learning processes. If it is not yet conducive, then a teacher or lecturer must work optimally to master, regulate and improve, and create a conducive atmosphere so that the learning process can run optimally to achieve the desired learning goals. Class management is not an easy and easy thing, let alone for teachers who have just fielded themselves into the world of education, for teachers who are already professional, they have felt how difficult it is to manage classes, but never teachers feel dry and then deter from managing classes every time they teach in class. The failure of a teacher to achieve teaching goals is in line with the inability of the teacher to manage the class, from failure it is achievement, learning of students is low, not in accordance with the standards or size limits that are determined, therefore classroom management is very important teacher competency mastered by the teacher within the framework of success teaching and learning process. Keywords: professional teachers, and Class management